Peripheral inflammatory markers indicate microstructural damage within periventricular white matter hyperintensities in Alzheimer's disease: A preliminary report. Issue 1 (21st January 2017) - Swardfager, Walter; Yu, Di; Ramirez, Joel; Cogo‐Moreira, Hugo; Szilagyi, Gregory; Holmes, Melissa F.; Scott, Christopher J.M.; Scola, Gustavo; Chan, Pak C.; Chen, Jialun; Chan, Parco; Sahlas, Demetrios J.; et al.
Abstract: Introduction: White matter hyperintensities (WMH) presumed to reflect cerebral small vessel disease and increased peripheral inflammatory markers are found commonly in Alzheimer's disease (AD), but their interrelationships remain unclear. Methods: Inflammatory markers were assayed in 54 elderly participants ( n  = 16 with AD). Periventricular WMH were delineated from T1, T2/proton density, and fluid‐attenuated magnetic resonance imaging using semiautomated fuzzy lesion extraction and coregistered with maps of fractional anisotropy (FA), a measure of microstructural integrity assessed using diffusion tensor imaging. Results: Mean FA within periventricular WMH was associated with an inflammatory factor consisting of interleukin (IL)‐1β, tumor necrosis factor, IL‐10, IL‐21, and IL‐23 in patients with AD (ρ = −0.703, P  = .002) but not in healthy elderly (ρ = 0.217, P  = .190). Inflammation was associated with greater FA in deep WMH in healthy elderly (ρ = 0.425, P  = .008) but not in patients with AD (ρ = 0.174, P  = .520). Discussion: Peripheral inflammatory markers may be differentially related to microstructural characteristics within the white matter affected by cerebral small vessel disease in elders with and without AD.